Practical supplements for prevention and management of migraine attacks: a narrative review - Hajhashemy, Zahra; Golpour-Hamedani, Sahar; Eshaghian, Niloofar; Sadeghi, Omid; Khorvash, Fariborz; Askari, Gholamreza (Frontiers in Nutrition, 2024)
Background: Migraine is one of the most debilitating neurological disorders that causes frequent attacks of headaches and affects approximately 11% of the global population.Deficient or even insufficient levels of vital nutrients would increase the severity and frequency of migraine attacks. Therefore, we aimed to examine the practical supplements for the prevention and management of migraine attacks.Method: This narrative review study was conducted by searching PubMed, ISI web of science, EMBASE, Google Scholar, and Scopus using the keywords of "dietary supplement" and "migraine" plus their MeSH terms. Original articles published in English language from their inception to July 27 th , 2024, studies that investigated adult population (aged >18 years), and those assessing the impact of intended nutrient supplementation on clinical symptoms of migraine were included in the study.Result: Oxidative stress and low intake of antioxidants would be risk factors for migraine attacks by inducing inflammation. The secretion of inflammatory cytokines, such as tumor necrosis factor (TNF)-a, would lead to neuroinflammation and migraine episodes by increasing the cellular permeability and interactions. Evidence also indicated a direct association between phases of migraine attacks and calcitonin gene-related peptide (CGRP), mitochondrial disorders, monoaminergic pathway, disruption in brain energy metabolism, and higher serum levels of glutamate and homocysteine. Therefore, supplementation with nutrients involved in mitochondrial function, brain energy metabolism, and even methyl donors would relieve migraine attacks.Evidence indicated that supplementation with riboflavin, omega-3 fatty acids, alpha lipoic acid, magnesium, probiotics, coenzyme Q10, ginger, and caffeine would have 4 favorable effects on migraine patients. However, more prospective studies are required to evaluate the effect of other nutrients on migraine patients.